Development and application of devices based on surface plasmon resonance - Lebyedyeva, T.S.; Minov, Y.D.; Sutkovyi, P.G.; Frolov, Y.O.; Shpylovyy, P.B.; Starodub, M.F. (Кібернетика та комп’ютерні технології, 2020)
The purpose of the paper is to present the development of “Plasmontest” series devices that can be used for laboratory applications, as portable field-research devices and to carry out a comparison of optical circuits of SPR devices, their capabilities and operational characteristics during biochemical and physical experiment.